Formaldehyde and acetaldehyde emissions from residential wood combustion in Portugal - Cerqueira, Mário; Gomes, Luís; Tarelho, Luís; Pio, Casimiro (Atmospheric Environment, 2013)
A series of experiments were conducted to characterize formaldehyde and acetaldehyde emissions from residential combustion of common wood species growing in Portugal. Five types of wood were investigated: maritime pine (Pinus pinaster), eucalyptus (Eucalyptus globulus), cork oak (Quercus suber), holm oak (Quercus rotundifolia) and pyrenean oak (Quercus pyrenaica). Laboratory experiments were performed with a typical wood stove used for domestic heating in Portugal and operating under realistic home conditions. Aldehydes were sampled from diluted combustion flue gas using silica cartridges coated with 2,4-dinitrophenylhydrazine and analyzed by high performance liquid chromatography with diode array detection. The average formaldehyde to acetaldehyde concentration ratio (molar basis) in the stove flue gas was in the range of 2.1–2.9. Among the tested wood types, pyrenean oak produced the highest emissions for both formaldehyde and acetaldehyde: 1772 ± 649 and 1110 ± 454 mg kg−1 biomass burned (dry basis), respectively. By contrast, maritime pine produced the lowest emissions: 653 ± 151 and 371 ± 162 mg kg−1 biomass (dry basis) burned, respectively. Aldehydes were sampled separately during distinct periods of the holm oak wood combustion cycles. Significant variations in the flue gas concentrations were found, with higher values measured during the devolatilization stage than in the flaming and smoldering stages.
Keywords: Acetaldehyde; Biomass combustion; Emissions; Formaldehyde; Wood stove

Emission factors from residential combustion appliances burning Portuguese biomass fuels - Fernandes, A. P.; Alves, C. A.; Goncalves, C.; Tarelho, L.; Pio, C.; Schimdl, C.; Bauer, H. (Journal of Environmental Monitoring, 2011)
Smoke from residential wood burning has been identified as a major contributor to air pollution, motivating detailed emission measurements under controlled conditions. A series of experiments were performed to compare the emission levels from two types of wood-stoves to those of fireplaces. Eight types of biomass were burned in the laboratory: wood from seven species of trees grown in the Portuguese forest (Pinus pinaster, Eucalyptus globulus, Quercus suber, Acacia longifolia, Quercus faginea, Olea europaea and Quercus ilex rotundifolia) and briquettes produced from forest biomass waste. Average emission factors were in the ranges 27.5-99.2 g CO kg-1, 552-1660 g CO2 kg-1, 0.66-1.34 g NO kg-1, and 0.82-4.94 g hydrocarbons kg-1 of biomass burned (dry basis). Average particle emission factors varied between 1.12 and 20.06 g kg-1 biomass burned (dry basis), with higher burn rates producing significantly less particle mass per kg wood burned than the low burn rates. Particle mass emission factors from wood-stoves were lower than those from the fireplace. The average emission factors for organic and elemental carbon were in the intervals 0.24-10.1 and 0.18-0.68 g kg-1 biomass burned (dry basis), respectively. The elemental carbon content of particles emitted from the energy-efficient "chimney type" logwood stove was substantially higher than in the conventional cast iron stove and fireplace, whereas the opposite was observed for the organic carbon fraction. Pinus pinaster, the only softwood species among all, was the biofuel with the lowest emissions of particles, CO, NO and hydrocarbons.
The following values have no corresponding Zotero field: publisher: The Royal Society of Chemistry
Keywords: Biomass combustion; Emission factors; Wood stove (voyant)